2012
DOI: 10.1111/j.1463-1318.2012.03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher rate of colorectal cancer among patients with pyogenic liver abscess withKlebsiella pneumoniaethan those without: an 11‐year follow‐up study

Abstract: Patients with K. pneumoniae PLA had a significantly higher rate of subsequent CRC than did patients with non-K. pneumoniae PLA. Colonoscopy is recommended to detect occult colonic malignancy in patients with PLA, particularly for patients over 60 years of age and with K. pneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 29 publications
(38 reference statements)
1
41
2
Order By: Relevance
“…This was obviously higher than those of the previous reports regarding pathogens in the similar geographical area [28,32,33,34]. A retrospective, 11-year follow-up study for PLA asserted that patients with K. pneumoniae PLA had a significantly higher rate of subsequent CRC than did patients with non- K. pneumoniae PLA [35]. Another study also reported that the percentage of K. pneumoniae in abscesses of colonic origin was higher than that of other origins [15].…”
Section: Discussioncontrasting
confidence: 54%
“…This was obviously higher than those of the previous reports regarding pathogens in the similar geographical area [28,32,33,34]. A retrospective, 11-year follow-up study for PLA asserted that patients with K. pneumoniae PLA had a significantly higher rate of subsequent CRC than did patients with non- K. pneumoniae PLA [35]. Another study also reported that the percentage of K. pneumoniae in abscesses of colonic origin was higher than that of other origins [15].…”
Section: Discussioncontrasting
confidence: 54%
“…It is uncommon for colorectal cancer to present with liver abscess and this is reported to occur in ≤5% of patients (20,21).The incidence of abscess formation due to colorectal cancer is highest in the liver, followed by the lungs, and cases of endocarditis and meningitis have also been reported (8)(9)(10)(11)(12)(13)(14)(15)(16). However, to the best of our knowledge there has only been 1 reported case of early colorectal cancer associated with a liver abscess (1), in addition to 2 cases of multiple abscesses due to colorectal cancer (12,16); therefore, the patient in the present case report is the first to be reported with multiple abscesses caused by early rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge there has only been 1 reported case of early colorectal cancer associated with a liver abscess (1), in addition to 2 cases of multiple abscesses due to colorectal cancer (12,16); therefore, the patient in the present case report is the first to be reported with multiple abscesses caused by early rectal cancer. The majority of the bacteria isolated from abscesses associated with colorectal cancer are gram negative rods such as Klebsiella (50.0%) or Fusobacterium (6.90%) species (14,15). Klebsiella with the same antibiotic sensitivity profile was isolated …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations